2017
DOI: 10.1051/0004-6361/201730785
|View full text |Cite
|
Sign up to set email alerts
|

Structural and dynamical modeling of WINGS clusters

Abstract: Context. We study the distribution of galaxies in nearby clusters to shed light on the evolutionary processes at work within clusters and prepare for a full dynamical analysis to be conducted in forthcoming papers of this series. Aims. We use the Wide-field Nearby Galaxy-clusters Survey (WINGS) database complemented with literature data. We assign galaxy membership to individual clusters, then select a sample of 67 clusters with at least 30 spectroscopic members each. 53 of these clusters do not show evidence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 75 publications
6
28
0
Order By: Relevance
“…As a function of cluster-centric distance, close to z = 0 the fraction of quenched galaxies grows toward the cluster center. This is in good agreement with the results obtained from observational studies based on different surveys such as WINGS (Cava et al 2017) and SAMI (Brough et al 2017). However, at earlier times, between z ∼ 1 and z ∼ 0.5, this trend reverts, showing a fraction of quenched galaxies that grows towards the cluster outskirts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As a function of cluster-centric distance, close to z = 0 the fraction of quenched galaxies grows toward the cluster center. This is in good agreement with the results obtained from observational studies based on different surveys such as WINGS (Cava et al 2017) and SAMI (Brough et al 2017). However, at earlier times, between z ∼ 1 and z ∼ 0.5, this trend reverts, showing a fraction of quenched galaxies that grows towards the cluster outskirts.…”
Section: Discussionsupporting
confidence: 91%
“…One of the first indications that the environment plays a fundamental role in driving the evolution of galaxies was the morphology-density relation (Dressler 1980(Dressler , 1984. Observational studies have shown that in high density environments there is a greater fraction of galaxies with early-type morphology than in low density environments, and that the fraction of early-type galaxies in clusters rises toward the cluster's center (Brough et al 2017;Cava et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As far as NG systems, they display a distinct feature with a depression in the central region and also a likely higher infall rate associated with galaxies in the Faint stacked VDP. These findings corroborate the Cava et al (2017) results for regular and irregular systems.…”
Section: Discussionsupporting
confidence: 90%
“…Struble 1979;den Hartog & Katgert 1996;Pimbblet et al 2014). Recent studies indicate an important difference between VDPs with respect to the dynamical state of galaxy clusters (see Hou et al 2009;Cava et al 2017;Costa et al 2018;Bilton & Pimbblet 2018). In Figure 2 we plot the VDPs for all galaxy families in two versions, binned and cumulative.…”
Section: Velocity Dispersion Profilesmentioning
confidence: 96%